Analisis Efektivitas dan Kontribusi Penerimaan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) dan Pajak Air Tanah dalam Rangka Peningkatan Pendapatan Asli Daerah Kota Gorontalo Tahun 2018-2022 - Hartati Tuli; Siti Pratiwi Husain; Melati Putriani Idris (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to determine the effectiveness and contribution of revenue from Land and Building Rights Acquisition Fees and Ground Water Tax in the context of increasing local original income in Gorontalo City. This research uses quantitative research methods. The data source used in this research is secondary data, namely the type of data published by BKD and related institutions. The data in this research is in the form of documentation of target reports and the realization of regional taxes in Gorontalo City. The data analysis technique in this research is descriptive quantitative analysis using the Microsoft Excel application. The research results show that 1. The effectiveness of Land and Building Rights Acquisition Fees on Original Regional Income in 2018-2022 is in the quite effective category because it has an average of 87.09%. 2. The effectiveness of Ground Water Tax on Original Regional Income in 2018-2022 has an overall average value of 47.24% and is included in the ineffective criteria. 3. The contribution of Land and Building Rights Acquisition Fees to Original Regional Income for 2018-2022 has a value of 4.77% so it is included in the very low criteria. 4. The contribution of Groundwater Tax to Original Regional Income for 2018-2022 has an overall average value of 0.044% and is included in the very poor criteria.